Livelihood of Street Vendors During Covid-19 Lockdown in Bangladesh: Earnings Break Off Expenses Remain - Mohammad Nur Ullah (Indonesian Journal of Social Research (IJSR), 2021)
On March 8, 2020, the first case of covid-19 was discovered in Bangladesh. As a result, the government decided to shut down all sectors for a certain period when the whole world was battling the first wave of Covid-19. After one year of the first wave, the second wave has recently hit the planet affecting almost all the countries including Bangladesh. Like all other sectors, street vending has been encountered and felt severe distress regarding the vendors’ livelihood. This study aims to explore the livelihood of street vendors during covid-19 in Bangladesh. This study features an in-depth interview of 15 street vendors to document their experiences during lockdown due to covid-19. This study is based on a qualitative approach with a purposive sampling technique. This study found lockdown is a significant burden for street vendors, leaving them with no other choice for earning money. During the lockdown, they expend savings, borrow money from others, take out loans, sell home furniture, and obtain money from their parents to fulfil their needs and demands. In order to improve this situation of street vendors, the government should take necessary steps with adequate financial and food assistance so that the vendors can survive during this lockdown.